Antimicrobial activity and spectroscopic characterization of surfactin class of lipopeptides from Bacillus amyloliquefaciens SR1. (March 2019) - Nanjundan, Jaivel; Ramasamy, Rajesh; Uthandi, Sivakumar; Ponnusamy, Marimuthu
Abstract: A bacterial isolate screened from wet land soil sample, found to posses antimicrobial activity against an array of fungal plant pathogens viz., Rhizoctonia solani, Sclerotium rolfsii, Alternaria solani, Fusarium oxysporum under in vitro dual culture plate assay. Further the isolate was identified into Bacillus amyloliquefaciens based on 16S rRNA sequencing. The antimicrobial fraction from the extracellular supernatant of the isolate comprises chiefly of surfactin molecules and also iturin and fengycin group of compounds. The surfactins were partially purified by tangential flow ultra-filtration and quantified with liquid chromatography yielding 316.1 mg L −1 . Further the surfactin molecules were characterized by HPLC separation, FT-IR, LC-MS spectroscopy and PCR amplification of antibiotic genes. The surfactin molecule with m/z 1022 performed for MS-MS fragmentation and produced two different patterns of ion dissociation. Graphical abstract: Image 1 Highlights: SR1 isolate exhibited potential antifungal activity against fungal plant pathogens. Surfactin class of lipopeptides were chiefly produced by SR1 isolate. Biosynthesis of lipopeptides by SR1 isolate were supported with spectroscopic data.